Influence of hydrogen on electrical and optical properties of ZnO films - Kim, Y. H.; Karazhanov, S. Zh.; Kim, W. M. (WILEY-V C H VERLAG GMBH, 2011)
Electrical and optical properties of H doped ZnO films have been studied experimentally for different H concentrations before and after annealing, as well as theoretically by first-principles calculations. It is found that electrical resistivity of the H doped ZnO increases when increasing the substrate temperature in the range 25-300 degrees C. Carrier concentration and mobility measured by Hall method in as-grown samples are larger than those of annealed ones. The short-wavelength edge of the transmission spectrum of annealed ZnO is found to shift toward lower energies compared to as-grown samples. The band gap estimated from the measured transmission spectra of as grown ZnO increases with increasing H concentration, thus demonstrating the Burstein-Moss effect. However, it decreases in samples annealed at 300 degrees C showing suppression of the Burstein-Moss effect. Possible defect models explaining the reason for the suppression are discussed. The results can be explained by formation of H-2 molecules in annealed ZnO. (C) 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: OXIDE